KEEFEKTIFAN MODEL PEMBELAJARAN EXPLICIT INTRUCTION BERBANTUAN FILLING AND PACKING TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI LUAS DAN VOLUME BANGUN RUANG SISWA KELAS V SD PANJANG 03 - widiastuti, ayu (Universitas Muhammadiyah Gresik, 2023)
This study was conducted based on observations and interviews with teachers of class V at SDN Panjang 03, class A and B. The teacher used the lecture method combined with discussion, where the results of the discussion were only collected without being discussed further. The results of interviews with teachers and students show that the material that is difficult to understand is about the properties of light. So, we need approaches and learning methods that can support students in understanding the material. Among the approaches that teachers can use is the explicit instruction approach which uses the experimental method. This study is an experimental research using a Quasi Experiment Design. The research population consisted of 50 students of class V SDN Panjang 03, namely class A and B. The statistical analysis used here included independent t-test, simple linear regression testing, and paired sample t-test using SPSS software. Based on the analysis of the data in this study, several important findings were found. First, there are differences in learning between the experimental and control classes. The average learning score of the experimental class was 65.59, while the control class reached 55.33. So, it can be concluded that the use of explicit instructions using filling and packing media has a different impact on students' understanding of concepts. Second, the results of the paired sample t-test showed that there was a significant increase in the students' conceptual understanding abilities using the explicit instruction model using filling and packing media. A significance value of 0.006 > 0.05 proves that there is a significant increase in the results of students' conceptual understanding abilities. Third, simple linear regression testing shows a significance value of 0.034 <0.05 which indicates the use of the explicit instruction model with filling and packing media has a significant effect on students' conceptual understanding skills at Panjang 03 Elementary School. This study concluded that explicit instruction learning using filling and packing media can help students absorb material about the area and volume of geometric shapes.